Urinary levels of catecholamines among individuals with and without sleep bruxism - Seraidarian, Paula; Seraidarian, Paulo Isaias; Cavalcanti, Bruno das Neves; Marchini, Leonardo [UNESP]; Claro Neves, Ana Christina (Springer Heidelberg, 2009)
Sleep bruxism (SB) is characterized by repetitive and coordinated mandible movements and non-functional teeth contacts during sleep time. Although the etiology of SB is controversial, the literature converges on its multifactorial origin. Occlusal factors, smoking, alcoholism, drug usage, stress, and anxiety have been described as SB trigger factors. Recent studies on this topic discussed the role of neurotransmitters on the development of SB.Thus, the purpose of this study was to detect and quantify the urinary levels of catecholamines, specifically of adrenaline, noradrenaline and dopamine, in subjects with SB and in control individuals.Urine from individuals with SB (n = 20) and without SB (n = 20) was subjected to liquid chromatography. The catecholamine data were compared by Mann-Whitney's test (p a parts per thousand currency sign 0.05).Our analysis showed higher levels of catecholamines in subjects with SB (adrenaline = 111.4 A mu g/24 h; noradrenaline = 261,5 A mu g/24 h; dopamine = 479.5 A mu g/24 h) than in control subjects (adrenaline = 35,0 A mu g/24 h; noradrenaline = 148,7 A mu g/24 h; dopamine = 201,7 A mu g/24 h). Statistical differences were found for the three catecholamines tested.It was concluded that individuals with SB have higher levels of urinary catecholamines.
Keywords: Sleep bruxism; Etiology; Catecholamines; Adrenaline; Noradrenaline; Dopamine; Urine